The Influence of Location on The Decision to Stay at Swiss- Belhotel Harbor Bay - ., Winny; Edy Wibowo, Agung; Lubis, Arina Luthfini (Jurnal Manajemen Pelayanan Hotel, 2024)
This study investigates the influence of hotel location on guests' decisions to stay at Swiss-Belhotel HarbourBay, a well-known hotel in Batam, Indonesia. The hotel offers all of the necessary amenities, and its workersprovide excellent service. The hotel's position, in a row of commercial shophouses in Harbor Bay and remotefrom major roads, is thought by hotel management to have an impact on the number of tourist visits, which isless than ideal. The study's goal is to research the relationship between hotel location and guest decision toremain, identify the important factors that influence guest decision to stay, and determine the impact on hotelroom sales. The study used a quantitative techniques methodology. The findings indicate that hotel location iscritical in deciding hotel location, with elements such as access, visibility, traffic, parking, and environment allinfluencing guests' decisions to stay. The study also identifies the factors that influence a guest's decision tostay, including product selection, brand selection, dealer selection, purchase timing, purchase quantity, andpayment method. The study's findings have major significance for hotel management, emphasizing thenecessity to shift hotel locations to boost overall hotel room sales. The alternative hypothesis is proven wherehotel location influences guest’s decision to stay with the formulation Y = 45.546 + 0.756X with a coefficient ofdetermination of 64.9%. This research suggests that hotels need to consider the location of a hotel beforebuilding a hotel so that it is easily accessible to potential guests.Keywords: Hotel Location, Guest’s Decision to Stay, Accessibility